Digital transformation management for agile organizations : a compass to sail the digital world - Bresciani, Stefano; Ferraris, Alberto; Romano, Marco; Santoro, Gabriele (Emerald Publishing Limited, 2021)
Digital Transformation Management for Agile Organizationshighlights and explores new dynamics regarding how current digital developments globally scale, by examining the threats, as well as the opportunities these innovations offer to organizations of all kinds.